Prevention Strategy of Violence in Pesantren - Arinal Rahmati; Fadhil Mubarak (The Institute of Research and Service Community IPMAFA Pati, 2023)
Violence such as beatings, intimidation, sexual harassment, and other forms often occur in many Pesantren. Cases of violence in Pesantren tarnished the name of Pesantren collectively, received stigma from various groups, and diminished public trust in Pesantren regarding the safety of students. Violence and bullying in Pesantren imply the significance and urgency of preventing violence and creating a safe Pesantren environment. Prevention of violence in Pesantren needs to be done with an effective strategy and a comprehensive approach. This paper aims to describe strategies for preventing violence in Pesantren and their relevance to various forms of violence in Pesantren, including bullying and sexual harassment. The method used in this study is a qualitative method with a case study approach. The data in this study are primary data obtained by observation, in-depth interviews, and documentation. The results of the study found that the prevention strategies used at Dayah Ummul Ayman included strengthening the supervisory function at the layer closest to the santri, continuing counseling on anti-violence in Pesantren, teaching commendable moral values, and internalizing commendable moral values. This paper is weak in generalization due to the use of qualitative methods. The researcher recommends that future researchers may use mixed methods in research on violence in Pesantren to produce more thorough and comprehensive findings.